Transfiks dan I‘lāl pada Konstruksi Fi‘il Mu‘tal dalam Animasi Saladin - Mahesa, Dzikri Cahya; Akmaliyah, Akmaliyah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the relationship between transfixation and i‘lāl in the formation of Arabic weak verbs by examining the transformation from underlying forms to surface forms. This study employed qualitative content analysis using morphological and morphophonemic approaches. The data were collected from the first episode of Saladin: The Animated Series through non-participatory observation and note-taking techniques. Data analysis involved identifying roots, determining wazan, applying transfixation, reconstructing underlying forms, and analyzing i‘lāl to produce surface forms. The study identified 260 verb tokens, from which 127 verb patterns were selected as research data, consisting of 80 strong verbs and 47 weak verbs. The findings reveal that transfixation alone is sufficient to generate the correct forms of strong verbs, whereas weak verbs require i‘lāl to transform underlying forms into acceptable surface forms. These findings demonstrate that transfixation and i‘lāl constitute complementary and sequential processes within Arabic internal modification. This study contributes to Arabic morphological theory by integrating roots, wazan, transfixation, underlying forms, i‘lāl, and surface forms into a unified analytical framework for explaining weak verb formation.